Biogenic production of palladium nanocrystals using microalgae and their immobilization on chitosan nanofibers for catalytic applications - Eroglu, Ela; Chen, X.; Bradshaw, M.; Agarwal, V.; Zou, J.; Stewart, S.; Duan, X.; Lamb, R.; Smith, S.; Raston, C.; Iyer, K. (2013)
Spherical palladium nanocrystals were generated from aqueous Na 2[PdCl4] via photosynthetic reactions within green microalgae (Chlorella vulgaris). Electrospun chitosan mats were effective for immobilizing these biogenic nanocrystals, as a material for recycling as a catalyst for the Mizoroki-Heck cross-coupling reaction. This photosynthetically-driven metal transformation system can serve as a good candidate for an environmentally-friendly method for the synthesis of metal nanocatalysts. © The Royal Society of Chemistry 2013.